(untitled) (Annual of the Faculty of Philosophy in Skopje, 2024)
Throughout history, families have undergone significant and profound changes. From the pre-industrial era to the present day, family structures have evolved due to industrialization, technological advancements, and shifting societal values. In the pre-industrial period, families focused on imparting essential skills to children, with women primarily managing household affairs and men assuming authoritative roles. However, industrialization brought about numerous changes in family life: family members joined the workforce, women gained prominence in public life, and traditional gender roles shifted. The emergence of capitalism altered economic dynamics, emphasizing individualism. Technological progress further transformed society, impacting medicine, communication, and daily life. Today, marriage rates have significantly declined, divorce rates have increased, fertility rates are lower, and marriage and childbirth are being postponed. This study aims to provide an overview of the characteristics and lifestyles of families before industrialization and to analyze the influence and changes in families brought about by the effects of industrialization.